Comparison of some hematological and serum biochemical variables in kangal akkaraman, texel and Île de france ewes in lactation period within sivas province - Mehmet Ekici; Abdurrahman Takcı; Mehmet Buğra Kıvrak (Eurasian Journal of Veterinary Sciences)
Aim: In this study, it was aimed to compare some hematological and biochemical variables in Kangal Akkaraman, Texel, and Île de France sheep breeds in the lactation period in Sivas province. Materials and Methods: A total of 120 ewe from three breeds (Kangal Akkaraman = 40, Texel = 40, Île de France = 40) who were clinically healthy nonpregnant and lactating (40-60 days) were used in the study. Hematological and biochemical variables analysis were performed using automatic cell counting and autoanalyzer devices. Results: There was no significant difference in WBC, Hb, MCHC, MPV levels between ewe breeds (p>0.05). RBC value was higher in Kangal Akkaraman than others (p<0.05). PCV values were higher in Kangal Akkaraman and Texel than Île de France (p<0.05). MCV and MCH values were lower in Kangal Akkaraman and Île de France compared to Texel (p<0.05). Although the PLT and RDW values were higher in Kangal Akkaraman (p<0.05), the PDW value was lower than others (p<0.05). Serum glucose level was lower in Texel than others (p<0.01). Serum total cholesterol, triglyceride, AST, ALT, albumin/globulin ratio, and Mg levels were not different between ewes (p>0.05). Serum total protein, albumin, globulin, and P levels were higher in Kangal Akkaraman compared to others (p<0.05). However, serum Ca levels were lower in Kangal Akkaraman than others (p<0.05). Conclusion: These results can constitute a reference value in these three sheep breeds reared in Sivas province, and help form a basis for future research.